A review of the deepwater cardinalfish genus Epigonus (Perciformes: Epigonidae) of the Western Indian Ocean, with description of two new species - Okamoto, Makoto; Gon, Ofer (Zootaxa, 2018)
The fishes of the genus Epigonus Rafinesque, 1810 in the Western Indian Ocean (including the Red Sea and the Gulf of Aden) are reviewed. Twelve species of the genus are recognized: Epigonus angustifrons Abramov & Manilo, 1987; E. denticulatus Dieuzeide, 1950; E. elongatus Parin & Abramov, 1986; E. exodon Okamoto & Motomura, 2012; E. lenimen (Whitley, 1935); E. macrops (Brauer, 1906); E. marimonticolus Parin & Abramov, 1986; E. marisrubri Krupp, Zajonz & Khalaf, 2009; E. pectinifer Mayer, 1974; E. robustus (Barnard, 1927); E. telescopus (Risso, 1810); E. waltersensis Parin & Abramov, 1986, and two new species, E. bispinosus n. sp. and E. idai n. sp. Epigonus bispinosus and E. idai belong to the E. constanciae group, defined as having a pungent opercular spine, more than 45 pored lateral-line scales, and lacking an isolated dorsal fin spine between the first- and second dorsal fins. Epigonus bispinosus differs from other members of the group in having two small spines on the symphysis of lower jaw, a pair of ribs on the last abdominal vertebra, 10 + 15 vertebrae, 31–33 gill rakers and lacking a maxillary mustache-like process. Epigonus idai differs from other members of the group in having a pair of ribs on the last abdominal vertebra, 4–5 tiny projections present on symphysis of lower jaw, 10 + 15 vertebrae, strongly ctenoid scales, and 28–29 gill rakers, and in lacking a maxillary mustache-like process. A key to the species, photographs, diagnoses, and distributions in the Western Indian Ocean are given.